2016
DOI: 10.1039/c6cp03749f
|View full text |Cite
|
Sign up to set email alerts
|

π–π stacking between polyaromatic hydrocarbon sheets beyond dispersion interactions

Abstract: High level ab initio calculations ranging from coupled cluster methods including explicitly correlated approaches to standard second order Møller-Plesset theory using spin scaling (SOS-MP2) have been performed on sandwich and slipped parallel dimer structures of a series of quasi one-dimensional acenes and on two-dimensional sheets containing the series pyrene to coronene encircled with two layers of benzene rings. Sandwich (graphitic AA type) and slipped parallel (AB type) structures were considered and, with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 83 publications
(149 reference statements)
5
55
0
Order By: Relevance
“…As the distance of the two parallel pyrene cores ( v ) decreased, the emission wavelength exhibited a bathochromic shift ( 1‐Me =445 nm, 1‐Et =415 nm, and 1‐ iso Bu =408 nm). The theoretical calculations suggested that pyrene formed an excimer with distances between the two parallel pyrene rings of 3.410 Å for v and 1.524 Å for l . These calculations support the model where 1‐Me forms an excimer in the crystal, resulting in an emission band at 445 nm.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…As the distance of the two parallel pyrene cores ( v ) decreased, the emission wavelength exhibited a bathochromic shift ( 1‐Me =445 nm, 1‐Et =415 nm, and 1‐ iso Bu =408 nm). The theoretical calculations suggested that pyrene formed an excimer with distances between the two parallel pyrene rings of 3.410 Å for v and 1.524 Å for l . These calculations support the model where 1‐Me forms an excimer in the crystal, resulting in an emission band at 445 nm.…”
Section: Resultssupporting
confidence: 68%
“…[25] The face-to-face pair of 1-Me and 1-Et slipped toward the short axis (s)o fp yrene by 4.316 and 5.320 ,r espectively,w hereas that of 1-isoBu slipped towards the long axis (l)o fp yrene by 5.342 .A st he distance of the two parallel pyrene cores (v)d ecreased, the emission wavelengthe xhibited ab athochromic shift (1-Me = 445 nm, 1-Et = 415 nm, and 1-isoBu = 408 nm). The theoretical calculations suggested that pyrene formed an excimer with distances between the two parallel pyrene rings of 3.410 for v and 1.524 for l. [26] These calculations support the model where 1-Me forms an excimeri nt he crystal,r esulting in an emission band at 445 nm. In contrast,f or 1-Et and 1-isoBu,p yrene chromophores were separated by alkyl groups,s uppressing excimer formation.T hese molecular orientations in the crystals are consistentw ith the observed emissions pectra (1-Me = 445 nm, 1-Et = 415 nm, and 1-isoBu = 408 nm).…”
Section: Herringbone Packingmentioning
confidence: 99%
“…Previous study shows that as the p system enlarges from benzene to pentacene,the interaction energy of p-p stacking significantly increases from À1.563 to À14.908 kcal mol À1 . [19] In PFC-1, the large p-conjugated pyrene were further stacking in AA arrangement along a-axis,a nd thus the augment of energy would be more significant. To illustrate the increment, the p-p interaction energies of PFC-1 dimer and trimer were calculated at the level of M06-2X/6-31G (d, p).…”
Section: Introductionmentioning
confidence: 99%
“…[19] In PFC-1, the large p-conjugated pyrene were further stacking in AA arrangement along a-axis,a nd thus the augment of energy would be more significant. [19] In PFC-1, the large p-conjugated pyrene were further stacking in AA arrangement along a-axis,a nd thus the augment of energy would be more significant.…”
mentioning
confidence: 99%
“…Because π–π interactions operate via surface‐to‐surface contacts, such interactions become important for large aromatic moieties as the π‐surface area increases . For example, the interaction energies (−Δ E ) of slipped‐parallel arene dimers increase in the order of benzene (5.6 kJ mol −1 ), naphthalene (15.6 kJ mol −1 ), and anthracene (27.0 kJ mol −1 ) as shown by high‐level ab initio calculations . In general, dispersion forces play an important role in the attractive terms in the overall π–π interactions, as long as the aromatic moieties have no polar substituents.…”
Section: Factors Affecting Complexationmentioning
confidence: 78%